Perfectly Peculiar! : Ripley's Believe It or Not! - Edited by Firpi, Jessica (USA Ripley Publishing, 2017)
Curioddities series, Perfectly Peculiar is sure to delight anyone who enjoys learning about the world of the weird! Readers will discover a skateboarding mouse, an underwater park, eyeball shaving and a man who's visited all 201 nations of the world!
Include Color Illustration, Index and Acknowledgment
Keywords: Curiosities and wonders